PREDIKSI KEPUASAN PENGGUNAAN LAPORAN KEUANGAN DIGITAL UMKM: INTEGRASI TECHNOLOGY ACCEPTANCE MODEL DAN IS SUCCESS MODEL - Meilinda Dwi Anugrah; Siska Aprianti; Nelly Masnila; Masayu Indah Ramaftadia Maharani; Stevy Josephin Bolley; Mey Safitri (Jurnal Riset Terapan Akuntansi, 2026)
This study aims to analyze the factors influencing user satisfaction in using Android-based digital financial reporting systems among MSMEs by integrating the Technology Acceptance Model (TAM) and Information System Success Model (ISSM). A quantitative explanatory approach was applied using survey data from 56 MSMEs supervised by the Prabumulih Cooperative and MSME Office. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results reveal that only User Perceived Value (UPV) significantly affects User Satisfaction, while Service Quality (SQ) and Ease of Use (EoU) show no significant effects. These findings indicate that the perceived usefulness and tangible benefits of the system are the main determinants of satisfaction and continued use of digital accounting applications. Practically, the study provides recommendations for application developers and MSME facilitators to focus on enhancing system usefulness to support the success of digital transformation among small enterprises. Keywords: SERVQUAL Model, Service Quality, Easy Of Use, User Perceived Value, Akuntansi Ku application.